American and Korean YouTuber's politeness strategies in reaction to Indonesian songs - Faridah Eka Fatmala (Journal of Research on English and Language Learning (J-REaLL), 2023)
Language as a communication tool aims to express one’s ideas and feelings. Through good communication, a person’s feelings or ideas can be realized well. The science of communicating well is explored in pragmatics, especially in communicating with the cultures of different countries. This research aims to examine the politeness strategy between American and Korean YouTubers in reacting to Indonesian songs. The data analysis in the study used cross-cultural pragmatic studies of politeness strategies by Brown and Levinson. The method used in this research is a qualitative descriptive method that is divided into three stages, namely the data collection stage, the data analysis stage, and the stage of interpreting the results of data analysis. The study results showed that American YouTubers use more polite strategies in reacting to Indonesian songs, Americans prefer to use direct politeness strategies because they prefer to express opinions directly. Meanwhile, Korean YouTubers in reacting to Indonesian songs choose soft and calm speech acts to express their opinion, so Koreans prefer to express their opinion with calm direct politeness speech.